Penerapan Sistem Full Day School sebagai Upaya Peningkatan Mutu Pembelajaran - Afifah, Nur; Mufidah, Ely (Indonesian Journal of Islamic Elementary Education, 2022)
Full-day school is a school process throughout the day or a teaching and learning process that is enforced from morning to evening. Learning quality at school enhances the success of schools in achieving learning goals. This study aims to determine the implementation of the full-day school system to improve the quality of learning at SDIT Gondang. The type of research used is a type of field research using a qualitative descriptive. Data collection techniques were carried out through interviews, observation, and documentation. Interviews were used to dig for in-depth data about the process of learning activities at SDIT Gondang. Observations are used as data reinforcement. Documentation is used as supporting data related to school profiles. The subjects of this study were school principals, vice principals for curriculum, and class teachers. The method of data analysis was carried out using data reduction analysis and concluding. The results showed that the implementation of full-day school to improve the quality of learning at SDIT Gondang was carried out with good educational planning, curriculum innovation, superior programs, habituation of good things, and extracurricular activities. Educational planning is embodied in the form of the school's vision, mission, and goals. The curriculum innovation used is the integration between the curriculum developed by the Ministry of Education and Culture, the Ministry of Religion, and the Foundation. The superior programs carried out are in the form of giving quizzes before class hours; TPQ/BTQ, tahsin, and tahfidz activities; and additional study hours. Furthermore, various extracurricular activities can be used to develop students' talents and interests.